How do landscape elements affect public health in subtropical high-density city: The pathway through the neighborhood physical environmental factors. (December 2021) - Fang, Yongli; Que, Qingmin; Tu, Ruoxiang; Liu, Yijun; Gao, Wei
Abstract: Purposes of this study are to explore associations between neighborhood landscape elements and public health in a subtropical high-density urban context, elucidate mediating effects of physical environmental factors, and propose corresponding neighborhood renewal strategies. Nine sampling sites were selected in Guangzhou, China, and public health data were collected from 438 participating residents using the MOS item short from health survey (SF-36 scale). Landscape elements of the neighborhoods, including greenness, blue spaces, walking trail systems, public squares, garden architecture, and dedicated sports spaces were mapped by unmanned aerial vehicle surveys. Seven physical environmental factors were measured: the heat stress index (HSI), relative humidity (RH), average wind speed (AWS), negative oxygen ions (NOI), <2.5 μM particulate matter (PM2.5 ), illumination (I), and noise (N). General linear models were used to explore differences between neighborhoods in landscape elements. Relationships between public health and both landscape elements and physical environmental factors, as well as the mediating pathways involved, were explored by correlation analysis and Mediation analyses. In subtropical high-density neighborhood, I, RH, HSI, NOI, and PM2.5 were significantly correlated with public health in the neighborhoods, as were greenness, blue spaces, walking trail systems, and public squares. Multiple mediation analysis showed that greenness, blue spaces and public squares significantly affected public health, with mediation by I, HSI and NOI. Landscape elements have close associations with public health, mainly mediated by effects on light, thermal, and atmospheric environments. These closely related landscape elements and physical environments need careful attention in neighborhood renewal efforts. Highlights: Landscape elements are related to public health in high-density neighborhoods. Landscape elements affect public health through physical environmental factors. Illumination, heat stress and negative oxygen ion levels are important mediator. Relative humidity and noisiness are not significant mediators. Improving neighborhood landscape and environmental quality to enhance public health.